2018
DOI: 10.1038/s41598-018-33603-8
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Membrane Supplementation in Formula-fed Rat Pups Improves Reflex Development and May Alter Brain Lipid Composition

Abstract: Human milk contains nutritional, immunoprotective and developmental components that support optimal infant growth and development. The milk fat globule membrane (MFGM) is one unique component, comprised of a tri-layer of polar lipids, glycolipids, and proteins, that may be important for brain development. MFGM is not present in most infant formulas. We tested the effects of bovine MFGM supplementation on reflex development and on brain lipid and metabolite composition in rats using the “pup in a cup” model. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
1
34
1
Order By: Relevance
“…Absolute and relative concentrations of total cholesterol, free cholesterol, and cholesterol ester in the prefrontal cortex and hippocampus did not differ between diet groups. Similar results were reported for brain lipid composition between mother-reared pups and pups receiving a formula without or with added dietary bMFGM (53). Brain lipids (including phosphatidylethanolamine, phosphatidylserine, and phosphatidylcholine) in the group receiving bMFGM were more similar to the mother-reared group.…”
Section: Discussionsupporting
confidence: 84%
“…Absolute and relative concentrations of total cholesterol, free cholesterol, and cholesterol ester in the prefrontal cortex and hippocampus did not differ between diet groups. Similar results were reported for brain lipid composition between mother-reared pups and pups receiving a formula without or with added dietary bMFGM (53). Brain lipids (including phosphatidylethanolamine, phosphatidylserine, and phosphatidylcholine) in the group receiving bMFGM were more similar to the mother-reared group.…”
Section: Discussionsupporting
confidence: 84%
“…[ 10 ] In a recent study in China, a formula supplemented with MFGM and lactoferrin significantly increased cognitive, language, and motor scores at 1 year of age. [ 11 ] Prior studies on MFGM (using the same source as the current report) in rat pups showed altered brain lipid composition [ 25 ] and increased expression of genes involved in synaptogenesis and polysialic acid synthesis. [ 26 ] Note that improved cognition observed in these studies may not necessarily be due to increased circulating ketone bodies, as there are other bioactive ingredients contained within the isolated bovine MFGM fraction including sialic acid, gangliosides, sphingomyelin, and lactoferrin.…”
Section: Discussionmentioning
confidence: 95%
“…While researchers are still making efforts to understand the functionalities of MFGM, there are already commercialized products supplementing MFGMs from bovine milk cream. The effectiveness of supplementation of MFGM in formula has been demonstrated in several independent cellular and animal studies, and clinical trials [25][26][27][28]. In Bovine milk based infant formulas have attempted to closely mimic the lipid composition of naturally originated breast milk.…”
Section: Breast Milk Fat Globulesmentioning
confidence: 99%